Parábola Vertical - Solís-Palma, Angie (My University, 2017)
Applet realizado en GeoGebra. Manipule los valores del vértice y la distancia entre el vértice y el foco. Observe la ecuación canónica, características y la gráfica de la parábola que se obtiene.

Applet made in GeoGebra. Manipulate the vertex values ​​and the distance between the vertex and the focus. Look at the canonical equation, characteristics and the graph of the parabola that is obtained.
Keywords: GeoGebra; Secciones cónicas; Conic sections; Parábola; Cálculo de variables; Variable calculation; Applet; Cálculo superior; Calculus